Effectiveness of Physical Therapy Combined with Electro Stimulation for Patients with Lumbar Part Disc Herniation - Andrius Švedas; Eglė Lendraitienė; Aiva Karpavičienė (Lithuanian Sports University, 2018)
Background. The aim of the study was to evaluate the effectiveness of physiotherapy combined with electro stimulation, for patients with spinal disc herniation in lumbar part. Methods. The study involved 38 people, 18 men and 20 women. The average age of all subjects was 29.84 ± 4.65 years. All subjects participated in the study for eight weeks, 30-45 minutes, three times a week. They were randomly  divided  in  to  three  groups:  two  experimental  and  one  control  group.  The  first  experimental  group   (12  people)  participated  in  physical  therapy  combined  with  electro  stimulation;  the  second  experimental  group   (14 people) participated in physical therapy combined with placebo (fake) electro stimulation, and the third (control) group (12 people) participated in physical therapy treatments. All groups before and after the treatment performed trunk (flexor, extensor, lateral musculature) muscular endurance tests (McGill), analogue pain scale evaluation, and SF - 36 questionnaire. Results. After eight weeks of physical therapy combined with electro stimulation average numbers of analogue pain scale results decreased statistically significantly by 2.17 ± 1.11 (p < .05), trunk extensors (33.00 ± 12.78), flexors (31.67 ± 9.15) and lateral left (20.25 ± 2.80) / right (19.50 ± 3.71) musculature differences were statistically significant (p < .05). Physical therapy and placebo (fake) electro stimulation group and physical therapy group did not show statistical significance for all the tests except for analogue pain scale test (1.29 ± 0.83 and 1.92 ± 1.08). Conclusion. Physical therapy combined with electro stimulation applied for eight weeks for 25-39-year-old adults suffering from lumbar part disc herniation is an effective way to enhance trunk flexors, extensors, right/left lateral muscular endurance and reducing lumbar part back pain. Keywords:  muscles, electro stimulation, physiotherapy, placebo